The Effect of Recruitment and Achievement Motivation on Discipline of Teacher Work at Private Kristen Kindergarten (TK) in Pontianak City - Angelina Larasati; Asrori Asrori; M Sukri (STKIP Singkawang, 2019)
This study aims to describe (1) Recruitment in Pontianak City Private Christian Kindergarten; (2) Achievement motivation in Pontianak City Private Christian Kindergarten; (3) work discipline of teachers in Pontianak City Private Christian Kindergarten; (4) The effect of recruitment on the work discipline of teachers in Pontianak City Private Christian Kindergarten; (5) The effect of achievement motivation on the work discipline of teachers in Pontianak City Private Christian Kindergarten; (6) The influence of recruitment and achievement motivation together on the work discipline of teachers in Pontianak City Private Christian Kindergarten. This research includes associative research with the approach used is a quantitative approach. The research method used in this study is a method of survey and analysis of research data using correlational study methods. The results obtained from this study are (1) Recruitment of teachers in Private City Christian Kindergarten in Pontianak through selection conducted by the school with the medium category score 107.61, and the obtained frequency is significant; (2) Achievement motivation of teachers in Private City Christian Kindergarten in Pontianak in terms of external motivation, and internal motivation is included in the low category with a score of 121.95; (3) The work discipline of teachers in Private Christian Kindergarten in Pontianak in terms of regular working hours, how to dress and how to work are in the medium category with a score of 144.00; (4) There is a significant influence between recruitment and teacher work discipline; (5) There is a significant influence between achievement motivation and teacher work discipline; (6) There is a significant relationship between recruitment and achievement motivation with teacher work discipline.